2010
DOI: 10.1016/j.engstruct.2010.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Truss vs solid modeling of tendons in prestressed concrete structures: Consequences on mechanical capacity of a Representative Structural Volume

Abstract: a b s t r a c tA comparative study is carried out on the mechanical behavior of a Representative Structural Volume of a prestressed concrete structure, using the state of the art of the numerical tools for engineers (and not the most recent developments of the academic research). The structural effect due to the presence of the tendons is carefully studied by comparing a classical truss finite element computation with a more sophisticated approach where the tendons are explicitly represented using a solid mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Besides allowing to use coarser meshes around the reinforcements, using bar elements simplifies the meshing procedure since the volumic and lineic meshes can be independent. This method allows to get good global results (force-displacement curve for instance), but is obviously not as accurate as a volumic representation of the reinforcements as shown by [5]. Indeed, two drawbacks can be underlined:…”
Section: Linking Truss and 3d Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides allowing to use coarser meshes around the reinforcements, using bar elements simplifies the meshing procedure since the volumic and lineic meshes can be independent. This method allows to get good global results (force-displacement curve for instance), but is obviously not as accurate as a volumic representation of the reinforcements as shown by [5]. Indeed, two drawbacks can be underlined:…”
Section: Linking Truss and 3d Modelmentioning
confidence: 99%
“…The intersection of Γ with the edges of mesh can be easily computed using the linear interpolation on the triangular element (cf. equation (5)). This implies that the quality of the geometries discretized using level-set functions will depend on their curvature (the less the curvature, the better the approximation).…”
Section: Numerical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these reinforcements are typically modeled in FE analyses using 1D elements, with beam or truss kinematics [4]. In some cases, where the three-dimensional effects of the tendon or rebar section have to be taken into account, full 3D models using conform meshes can be applied [8].…”
Section: Introductionmentioning
confidence: 99%
“…It consists in a numerical model of a representative structural volume (RSV) of a prestressed and reinforced concrete containment building, on which a pressure test is performed. This particular structure is strongly dependent on the prestressing tendons, which affect damage localization and failure mode [8]. In particular, previous studies have demonstrated an inclusion effect around the vertical tendon.…”
Section: Presentationmentioning
confidence: 99%